Perbandingan Karakteristik Fisiologis Atlet Ganda Putra dan Ganda Putri Bulu Tangkis Junior - Septina, Trisha Aryanti; Hasan, Muhammad Fahmi; Syafriani, Rini; Juniarsyah, Agung Dwi; Fathannisa, Tuliss Bial; Alviana, Irana Mery; Latief, Gifran Rihla Gifarka; Apriantono, Tommy (Indonesian Journal of Kinanthropology (IJOK), 2025)
Background: This study aims to describe and compare the physiological characteristics of junior men’s and women’s doubles athletes in badminton. Methods: Testing consists of anthropometric and physical ability tests. Anthropometry includes height, weight, BMI, fat mass, muscle mass. Physical ability tests include handgrip, sit & reach, counter movement jump, stroke stand balance, whole body reaction, 10m sprint, ilinois agility test, VO2max (multi stage sprint), anaerobic capacity (RAST Test). Statistical analysis using normality test and paired t-test. Results: The results showed significant differences in almost all anthropometric tests except BMI. There are significant differences in the components of hand grip ability, CMJ, 10m sprint, VO2max, anaerobic capacity and there are no significant differences in sit & reach ability, balance, reaction and agility. Conclusions: By utilizing all the findings, practical suggestions can be designed for junior badminton athlete coaches.